Mortality [compact disc, unabridged] - Hitchens, Christopher (Hachette Audio, 2012)
Throughout the course of his ordeal battling esophageal cancer, Hitchens adamantly and bravely refused the solace of religion, preferring to confront death with both eyes open. In a riveting account of his affliction, Hitchens poignantly describes the torments of illness, discusses its taboos, and explores how disease transforms experience and changes our relationship to the world around us. By turns personal and philosophical, Hitchens embraces the full panoply of human emotions.